Diversidade religiosa e ensino religioso: relações possíveis? Um olhar a partir de alunos e professores de escolas municipais de João Pessoa-PB - Nascimento, Fernanda Santos do (2016)
This work resulted from an ethnographic study aimed to understand if the religious diversity came into being in Religious Education classes and the contribution of its insertion in these classes from the point of view of students and teachers from three public schools in João Pessoa, Pernambuco, Brazil. In the first chapter the topic diversity were brought to discussion, multiculturalism, multiculturality and interculturality although they’re polysemous, they’re different in understanding of meaning usage, that sometimes are closer and sometimes are not, although these terms are used many often as synonyms of several cultural diversity. However, it is intended to make clear to the reader the meaning imposed to the cultural diversity terms throughout this work. In the second chapter was presented a reflection about the history of religious education panorama, approaching its nature from the period of colonization to the present day, emphasizing its inclusion in the draft Common National Base Curriculum. The third chapter highlights the ethnographic method, reflecting on the subtle differences in the field work and construction of data during the experience with the research subjects, showing who they are and the context which they’re inserted. In the fourth and final chapter, was done the analysis of the collected data in the field work, in order to respond to the needs of the research. Therefore, the presence of religious diversity in those public schools was notable in religious education classes, but it brings along the ways in which religious intolerance has gained ground, especially the prejudice against religions of African origin.